1998
DOI: 10.1007/pl00005212
|View full text |Cite
|
Sign up to set email alerts
|

Structure-dependent inhibitory action of the Aconitum alkaloids 14-benzoyltalitasamine and talitasamine in rat hippocampal slices

Abstract: In the present study the effects of the two Aconitum alkaloids 14-benzoyltalitasamine and talitasamine on neuronal activity were investigated in order to obtain further insight into structure-dependent effects of this group of alkaloids on central nervous activity. Both alkaloids are closely related to aconitine, the main alkaloid of plants of Aconitum species. However, they have shortened side chains at position C3 and C8 of the molecule. The experiments were performed as extracellular recordings of orthodrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…3. DDA reduction during processing of aconite roots by pressure-steaming technique and that they should not be entirely diminished from the drug (Ameri, 1998b;Yang et al, 1997).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…3. DDA reduction during processing of aconite roots by pressure-steaming technique and that they should not be entirely diminished from the drug (Ameri, 1998b;Yang et al, 1997).…”
Section: Resultsmentioning
confidence: 97%
“…Independent of the processing way chosen for herbal preparations, decomposition of DDAs should be achieved. Nevertheless, an appropriate minimal DDA content is still required to achieve its pharmacological effects while reducing its high toxicity (Ameri, 1998b;Yang et al, 1997).…”
Section: Pressure-steaming Techniquementioning
confidence: 98%
See 1 more Smart Citation
“…Anti‐epileptic studies revealed that the presence of an aromatic substituent is essential for anti‐epileptic activity. Aconitum compounds with aromatic substituent 6‐benzoylheteratisine, 1‐benzoylnapelline, lappaconitine and 14 benzoyltalatisamine inhibited rat hippocampal excitability more potently than heteratisine, napelline, lappaconidine and talatisamine, respectively [70–73]…”
Section: Pharmacology Of Aconitummentioning
confidence: 99%
“…[1] The precise neurophysiologic mechanism of Acn action is not completely known, but its main and most toxic component, aconitine, which is characterized by a steroidal alkaloid chemical structure, has been studied in the central nervous system of rats at the level of the hippocampus neuronal activity. [46] Specialized neurophysiological research, based on patch-clamp techniques mainly related to the neuron excitability process, has demonstrated that a low physiological Acn dose (10 −6 M) affects individual pre-synaptic rat neuron excitability by opening Na+ channels. [47]…”
Section: Discussionmentioning
confidence: 99%